Self-oscillations of unsaturated compounds concentrations in the oxidative carbonylation processes. 1. Processes of acetylene and phenylacetylene oxidative carbonylation - S. N. Gorodsky; K. Novakovich (Тонкие химические технологии, 2011)
This review is devoted to the results of concentrations oscillations phenomena study observed in the unsaturated compounds oxidative carbonylation reactions. These homogeneous reactions are catalyzed by metal complexes. The history of oscillations processes study is described, there theoretical and practical significance underlined. The wide description of the processes studying at the Department of chemical technology of basic organic synthesis in last years is brought. The first part of review is devoted to acetylene and phenylacetylene oxidative carbonylation processes describing.